Tuberculous pleuritis secondary to Mycobacterium bovis in a veterinarian. - Corcoran, J; Hallifax, R; Bettinson, H; Psallidas, I; Rahman, N (2014)
Mycobacterium bovis is a rare cause of tuberculosis in humans, but should be considered in individuals at risk secondary to medical comorbidities (notably immunocompromise) or occupational exposure. Most cases are secondary to reactivation of latent infection in elderly individuals although cases of primary infection still occur, usually involving animal-to-human transmission. Pleural fluid culture in the context of suspected tuberculous pleuritis is frequently negative and pleural biopsy significantly increases the likelihood of confirming the diagnosis histologically and microbiologically. Although thoracoscopic biopsies are the reference standard, closed pleural biopsies are an appropriate and more accessible alternative in the majority of cases - these should be done under direct ultrasound guidance to maximise diagnostic yield. Treatment for M. bovis infection is with prolonged combination anti-tuberculous therapy, using an alternative to pyrazinamide as the organism is inherently resistant to this drug.